MENGENALKAN PEMBAYARAN DIGITAL LEWAT QRIS UNTUK MELANCARKAN TRANSAKSI USAHA MIKRO DI DESA CIKOLELET - Farida, Farida; Effendi, Maya Syafriana; Wahyuni, Nur; Firdaus, Venus F; Rahayu, Maryati; Budilaksono, Sularso; Sovitriana, Rilla (Universitas Mataram, 2024)
Cikolelet Village is, as a tourist village, able to stimulate the economy of its residents. Many economic activities have grown due to the impact of many visitors to the village. Apart from natural tourism, many micro and household businesses support the circulation of economic and financial activities. Unfortunately, amidst the success of attracting tourists and increasing sales of locally produced goods, transaction payments are still conventional. This community service activity aims to introduce a digital payment system through QRIS to facilitate payments and increase sales. The service method is divided into three parts. They are planning, implementation, and evaluation. The Planning stage was done by the University LPPM team, from coordination with partners and collaboration between universities. The implementation phase by the member team consists of material presentations, discussions, questions, and answers, as well as direct practice in registering for QRIS. The evaluation stage was carried out to determine the level of interest of business actors in using QRIS. The result was that only around 34.6 percent of participants were interested and registered, while 65.4 percent were less concerned. Along with the era of technology and digitalization, people are required to be technologically literate in order to be able to compete. Services, both products and services as well as supporting facilities, must be improved to facilitate and increase mutual comfort.